PERILAKU PEMILIH PEREMPUAN ETNIS BATAK TOBA PADA PEMILIHAN LANGSUNG WALIKOTA DAN WAKIL WALIKOTA MEDAN TAHUN 2010 DI LINGKUNGAN XIV KELURAHAN SIDORAME TIMUR KECAMATAN MEDAN PERJUANGAN KOTA MEDAN - Susi Elfrida Marpaung (Universitas Medan Area, 2014)
Voter participation was the subject not the object of mobilization, so he has the independence to build awareness, formulating options as well as expressing his choice. This study highlights the problem of voter behavior Female Ethnic Batak Toba in Lingkungan XIV Kelurahan Sidorame Timur Kecamatan Medan Perjuangan Medan in the direct election of Mayor/ Deputy Mayor of first and second round of Field in 2010 by using the factors: 1) Ethnicity 2) Political Preferences Family 3) Gender 4) Identification of Party 5) Political Money 6) Image of the candidate. Studies using random sampling by involving women sample 79 ethnic Batak Toba. Results of the study it was concluded that candidate a dominant factor affecting voter behavior in the first and second rounds. It is evident from the distribution of the answers of respondents regarding the candidate's image, where the indicator lights placed first of four (4) indicators that are offered that as much as 79.